HISTORY OF THE COUNTRY AND INTERPRETATION OF THE FATE OF THE PEOPLE (Scientific journal of the Fergana State University, 2023)
The article deals with the lyrical expression of the dreams of the poet Khurshid Davron about the freedom of the country and the freedom of man in the lyrics of the 70-80s of the twentieth century.The past of the Motherland, the great history of our people and its bright future, the contradictions in the social and spiritual life, the heroes of the people who gave their lives for freedom, the victims of the Motherland, as well as the call for vigilance and alert not to be, indifference to several social occasions indifference, indifference to light. great ancestors are reflected in several poetic verses. Moreover, in the article you can see poetic poems written about the for compassion of the next generation.